BOOK REVIEW: RODICA FRENȚIU. “LIMBAJUL POETIC – ACT CREATOR ȘI ACTUALITATE CULTURALĂ: MODELUL CULTURAL JAPONEZ [POETIC LANGUAGE – CREATIVE ACT AND CULTURAL ACTUALITY: THE JAPANESE CULTURAL MODEL]”, CLUJ-NAPOCA: PRESA UNIVERSITARĂ CLUJEANĂ PUBLISHING HOUSE, 2017, 250 P. - Ioana-Ciliana TUDORICĂ (Studia Universitatis Babeş-Bolyai. Philologia, 2020)
Poetic Language – Creative Act and Cultural Actuality: the Japanese Cultural Model is a complex work that can be enjoyed by both researchers of Japanese language and culture, as well as readers passionate about Japan. The complexity of the issues addressed and the manner in which these matters have been analysed mark the volume as an important research point for both Japanese language students and researchers from numerous fields.